Audit of Current Practise of Transfer of Care From Child and Adolescent Mental Health Services (CAMHS) to Adult Mental Health Services (AMHS) in Devon Partnership NHS Trust - Lucia Curran (BJPsych Open, 2025)
Aims: The transfer of care from CAMHS to AMHS is often poorly managed which is distressing for young people and their families. The implications of poor transition include disengagement from services and deterioration in young people’s mental health.